POLICY ANALYSIS AND IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT IN PUBLIC ELEMENTARY SCHOOLS NORTH LOMBOK REGENCY - Etika Lailaturrahmah; Heri Hadi Saputra; Mohamad Mustari; Muhammad Makki; Fahruddin Fahruddin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
The School Literacy Movement (GLS) is a program implemented by the Indonesian government to foster literacy culture in elementary schools. The purpose of this study is to analyze the policy, implementation, and governance of GLS in Public Elementary Schools (SDN) in North Lombok Regency. The research approach used is qualitative research with a case study method. Data collection techniques used were interviews, observations, and documentation studies.The research data sources were the Department of Education, Culture, Youth, and Sports (Dikbudpora), school principals, teachers, and students. Data were analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The study's results reveal the views of policymakers and implementers regarding GLS. Policies related to GLS have not been implemented optimally because policymakers do not yet have derivative regulations, technical guidelines, or formal policies that serve as the basis for literacy implementation in schools. As a result, the implementation of GLS in schools is very diverse, generally only at the habituation stage, but its implementation is not yet evenly distributed, comprehensive, and consistent. This is also influenced by GLS governance, which has not been running optimally because planning, organising, implementing, coordinating, and controlling the program have not been carried out systematically.